2017
DOI: 10.1111/liv.13466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on survival of patients with hepatocellular carcinoma

Abstract: This study shows that smoking is an independent predictor of survival in hepatitis B virus/hepatitis C virus-infected patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…The Cox proportional hazards model was used to estimate the hazard ratios (HRs) relating risk factors to survival outcomes. The final multivariable model consisted of variables with clinical significance determined a priori (age, 15,16 sex, 15,16 tobacco history, 17,18 alcohol history, 15,17 cirrhosis, 19,20 and liver disease etiology [20][21][22][23][24] and variables that met significance in the univariable model. The final model estimated the HRs for diagnosis year groups, adjusting for ethnicity, HCC etiology, age, sex, tobacco and alcohol history, cirrhosis status, MELD score, Milan criteria status, and primary treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…The Cox proportional hazards model was used to estimate the hazard ratios (HRs) relating risk factors to survival outcomes. The final multivariable model consisted of variables with clinical significance determined a priori (age, 15,16 sex, 15,16 tobacco history, 17,18 alcohol history, 15,17 cirrhosis, 19,20 and liver disease etiology [20][21][22][23][24] and variables that met significance in the univariable model. The final model estimated the HRs for diagnosis year groups, adjusting for ethnicity, HCC etiology, age, sex, tobacco and alcohol history, cirrhosis status, MELD score, Milan criteria status, and primary treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies [79][80][81] identified assessed the association between smoking and survival amongst liver cancer patients (Supplementary table 3).…”
Section: Liver Cancer Smoking and Survival In Liver Cancer Patientsmentioning
confidence: 99%
“…In hepatocellular carcinoma patients with viral hepatitis, Shih et al [81] found that current smokers had worse liver cancer specific survival than never smokers (HR 1.25, 95% CI 1.09-1.44) and Holly et al [80] found that current smokers had worse overall survival than non-smokers (HR 2.41, 95% CI 1. 28-4.55).…”
Section: Liver Cancer Smoking and Survival In Liver Cancer Patientsmentioning
confidence: 99%
“…These scoring systems comprise the parameters BCLC stage, alpha‐fetoprotein level, tumour size and number, Child‐Pugh score, radiological tumour response and aspartate aminotransferase level. We also included other potentially clinically meaningful parameters regarding aetiology (alcohol abuse, hepatitis B and C, non‐alcoholic steatohepatitis), comorbidities (nicotine abuse, obesity, diabetes) and tumour growth pattern . In addition, we included the following potentially meaningful parameters indicating liver function: MELD, bilirubin, albumin and the international normalized ratio .…”
Section: Methodsmentioning
confidence: 99%